2018
DOI: 10.1093/femspd/fty005
|View full text |Cite
|
Sign up to set email alerts
|

RNase 7 but not psoriasin nor sPLA2-IIA associates with Mycobacterium tuberculosis during airway epithelial cell infection

Abstract: Tuberculosis is a disease caused by Mycobacterium tuberculosis (Mtb). Innate immunity is the first line of defense against Mtb and malfunctions in any of its components are associated with the susceptibility to the disease. Epithelial products such as host defense peptides (HDPs) are the first molecules produced to counteract the infection. Although a wide variety of HDPs are produced by epithelial cells only a few of them have been studied during Mtb infection. Here, we assessed the expression and production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The present time-course expression profiles in M. aurum infected THP1 macrophages indicates a downregulation of RNase3 and RNase6 after a short infection period followed by a significant upregulation at longer incubation times. Modulation of antimicrobial RNases following M. aurum infection are in agreement with previously reported results using M. tuberculosis (18, 24). In the literature there are other examples of AMPs downregulated upon mycobacteria infection, a process induced by the Mtb bacilli as a protection mechanism against the host innate armory (12, 30).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present time-course expression profiles in M. aurum infected THP1 macrophages indicates a downregulation of RNase3 and RNase6 after a short infection period followed by a significant upregulation at longer incubation times. Modulation of antimicrobial RNases following M. aurum infection are in agreement with previously reported results using M. tuberculosis (18, 24). In the literature there are other examples of AMPs downregulated upon mycobacteria infection, a process induced by the Mtb bacilli as a protection mechanism against the host innate armory (12, 30).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the researchers observed the specific recruitment and induction of eosinophils by lipomannan, a unique mycobacterial cell-wall component. Very recently, Rivas-Santiago and coworkers reported the overexpression of RNase7 in airway epithelial cells infected by M. tuberculosis (24). In our laboratory we have confirmed the antimycobacterial activity of recombinant RNase3 and RNase7 on M. vaccae in vitro and characterized the protein mechanism of action at the bacterial cell-wall (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies showed that RNase 7 is highly antimicrobial effective in low micromolar concentrations against Gram-positive and Gram-negative bacteria like S. aureus, P. aeruginosa, C. amycolatum, E. faecium, Mycobacterium vaccae , the yeast Candida (C.) albicans and Pichia pastoris and the dermatophyte T. rubrum (12, 16, 30, 3741). The known microorganisms susceptible to RNase 7 are listed in Table 1 (6, 7, 12, 1416, 25, 2931, 3750). The functional relevance of the antimicrobial activity of RNase 7 and its contribution to the antimicrobial capacity of stratum corneum was demonstrated by the use of antibodies that neutralized the antimicrobial activity of RNase 7.…”
Section: Antimicrobial and Ribonuclease Activitymentioning
confidence: 99%
“…It has been reported that RNase 7 exhibits antimicrobial activity against Mycobacterium vaccae at low micromolar concentrations (40). Furthermore, infection of airway epithelial cells with Mycobacterium tuberculosis led to induction of RNase 7 expression and an intracellular association of RNase 7 with Mycobacterium tuberculosis (50). This may suggest a direct antimicrobial effect of RNase 7 on Mycobacterium tuberculosis , but this has to be confirmed in further studies.…”
Section: Role Of Rnase 7 In Skin Diseasesmentioning
confidence: 99%